2018
DOI: 10.1371/journal.pone.0203641
|View full text |Cite
|
Sign up to set email alerts
|

Extended antibiotic treatment in salmon farms select multiresistant gut bacteria with a high prevalence of antibiotic resistance genes

Abstract: The high use of antibiotics for the treatment of bacterial diseases is one of the main problems in the mass production of animal protein. Salmon farming in Chile is a clear example of the above statement, where more than 5,500 tonnes of antibiotics have been used over the last 10 years. This has caused a great impact both at the production level and on the environment; however, there are still few works in relation to it. In order to demonstrate the impact of the high use of antibiotics on fish gut microbiota,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 97 publications
(104 reference statements)
3
61
1
1
Order By: Relevance
“…These observations suggest that there is a general trend of increasing resistance to oxytetracycline and sulpha‐trimethoprim of E. tarda isolates in aquaculture. It has been well documented that consistent long‐term exposure to antibiotics or overuse of antibiotics in aquaculture may result in the development of bacterial resistance (Higuera‐Llanten et al, ; Santos & Ramos, ; Usui et al, ). A study by Rico et al () reported that the commonly used antibiotics for the prevention and treatment of bacterial infection in Thailand were oxytetracycline, amoxicillin and sulpha‐trimethoprim.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that there is a general trend of increasing resistance to oxytetracycline and sulpha‐trimethoprim of E. tarda isolates in aquaculture. It has been well documented that consistent long‐term exposure to antibiotics or overuse of antibiotics in aquaculture may result in the development of bacterial resistance (Higuera‐Llanten et al, ; Santos & Ramos, ; Usui et al, ). A study by Rico et al () reported that the commonly used antibiotics for the prevention and treatment of bacterial infection in Thailand were oxytetracycline, amoxicillin and sulpha‐trimethoprim.…”
Section: Discussionmentioning
confidence: 99%
“…The other strains containing the genes sulI and qacΔE , in the typical structure of a class 1 integron, showed no gene cassettes in the variable region, which implies that the system has a great potential to incorporate and express new antibiotic resistance genes. Nonetheless, it is important to note that none of the antibiotic resistance genes to florfenicol and oxytetracycline described in both banks by Higuera-Llanten et al 2018 [14] are found in the integrons of the isolated bacteria. Currently, a complete metagenomic analysis is being carried out to find the relationship between these resistance determinants and these genetic elements that could probably be established in non-culturable bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…For this study, characterized banks of resistant bacteria to florfenicol and oxytetracycline isolated in our lab were used [14]. Shortly, four Atlantic salmon ( Salmo salar ) fish farms were chosen, located in the Aysén Region, North Patagonia, Chile.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations